Need-supportive coaching and engagement in Chinese high school football players: a serial mediation model - Jiang, Chuantong; Razak, Norsilawati Abdul; Rasyid, Nelfianty Mohd (Frontiers in Psychology, 2025)
IntroductionThis study aimed to investigate the relationship between need-supportive coaching behavior, subjective task value, goal orientation, and engagement among Chinese high school football players and propose four research hypotheses better to understand the determinants and mechanisms of athlete engagement.MethodsParticipants were 385 Chinese high school football players (228 boys; 157 girls; Mage = 16.07 years; SD = 1.15; range = 14–19 years) on 20 teams from 45 high schools using a proportional stratified random sampling method. Participants filled out previously validated questionnaires, including the Interpersonal Behaviors Questionnaire (IBQ), Subjective Task Value (STV), The Task and Ego Orientations Questionnaire (TEOSQ), and Athlete Engagement Questionnaire (AEQ). To address the hypothesis testing, this study utilized structural equation modeling (SEM) to analyze the proposed multiple mediation model.ResultsThe research results indicated that need-supportive coaching behavior had a significant direct (β = 0.121, Z = 3.667, p < 0.001) and indirect (β = 0.209, Z = 5.500, p < 0.001) effect on athlete engagement. Moreover, need-supportive coaching behavior positively predicted athlete engagement through subjective task value (β = 0.128, Z = 4.000, p < 0.001) and task orientation (β = 0.053, Z = 3.118, p < 0.001). Also, subjective task value and task orientation sequentially mediated the relationship between need-supportive coaching behavior and athlete engagement (β = 0.028, Z = 3.500, p < 0.001).DiscussionThe findings demonstrate that need-supportive coaching behavior, subjective task value, and task orientation are important factors in promoting athlete engagement. The study implies that encouraging and guiding coaches to adopt a need-supportive coaching style is an effective motivational strategy, which can not only directly predict athlete engagement, but also indirectly influence athlete engagement through subjective task value and task orientation.